Water-Deprived Parasitic Wasps (Pachycrepoideus vindemmiae) Kill More Pupae of a Pest (Drosophila suzukii) as a Water-Intake Strategy - Bezerra Da Silva, Cherre Sade (Sci Rep, 2019)
Most organisms must ingest water to compensate for dehydration. In parasitic wasps, the importance of water and the behaviors driving its consumption are poorly understood. Here, we describe a water-intake strategy of Pachycrepoideus vindemmiae, a parasitoid of spotted-wing drosophila (SWD, Drosophila suzukii). Longevity measurements indicated that P. vindemmiae benefits from drinking water and from host-feeding on the water-rich hemolymph of SWD pupae. After exposing wasps to different water regimens, we observed increased host-feeding in water-deprived wasps despite honey availability. This resulted in greater SWD mortality because the host-feeding process killed the pupae, and because wasps that engaged in greater host-feeding parasitized more hosts. Behavioral observations showed that the host-feeding time of water-deprived wasps doubled compared to water-fed individuals. Host-feeding did not affect parasitoid offspring mortality. We conclude that P. vindemmiae benefits from ingesting water and that it host-feeds on SWD pupae as a water-intake strategy. These are interesting findings not only because water has rarely been reported as a critical nutrient for adult parasitoids, but especially because preying for the purpose of hydration is not a common strategy in nature. This strategy enhances parasitoid survival and reproduction, with positive consequences for its host-killing capacity and potential as a biocontrol agent.